American law : an introduction - Friedman, Lawrence M. (Lawrence Meir), 1930-; Hayden, Grant M. (New York, NY : Oxford University Press, 2017)
This work provides an introduction to the American legal system for a broad readership. Its focus is on law in practice, on the role of the law in American society; and how the social context affects the living law of the United States.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 12, 2016).
Keywords: Law -- United States -- Popular works; Law; Laws of specific jurisdictions & specific areas of law